Mental toughness in elite adolescent football players: Exploring the role of motivational climate and coach-athlete relationships - Mesquita da Silva, S.; Felton, L.; Dias, C. S.; Fonseca, A. (International Journal of Sports Science & Coaching, 2025)
Mental toughness is an important predictor of desirable outcomes in sport, and so an essential mental ability for young athletes to develop. However, it remains unclear how mental toughness relates to distinct-yet-interacting features of several team psychosocial contexts, such as the motivational climate and the quality of coach-athlete relationship. This cross-sectional study tested the relative roles of coach-created motivational climate and coach-athlete relationship, and their interaction, in predicting variance in athlete mental toughness. Participants were 140 male elite adolescent athletes (aged 12 to 17 years) from the youth academy of a Portuguese Premier League football club. Hierarchical linear regressions showed that athletes` perceptions of an empowering coach-created motivational climate did not account for additional variance in mental toughness beyond that accounted for by coach-athlete relationship. In contrast, coach-athlete relationship accounted for additional variance beyond an empowering coach-created motivational climate. These results suggest that the concept of quality coach-athlete relationships is embedded within good coach leadership and highlight its relevance over broader motivational climate for healthy psychological development in youth athletes. A moderation analysis revealed a significant interaction between empowering coach-created motivational climate and coach-athlete relationship, with the positive association between empowering coach-created motivational climate and mental toughness increasing as coach-athlete relationship increased in quality. This result implies that the positive effect of motivational climate on mental toughness depends on there being high quality coach-athlete relationships. Future psychological interventions aimed at increasing mental toughness in young athletes should also contemplate the quality of coach-athlete relationship.